Organic frameworks confined Cu single atoms and nanoclusters for tandem electrocatalytic CO2 reduction to methane. Issue 1 (17th March 2022) - Zhao, Qinglan; Wang, Yian; Li, Meng; Zhu, Shangqian; Li, Tiehuai; Yang, Jixiang; Lin, Ting; Delmo, Ernest P.; Wang, Yinuo; Jang, Juhee; Gu, Meng; Shao, Minhua
Abstract: The electrochemical reduction reaction of carbon dioxide (CO2 RR) is considered to be an effective way to realize carbon neutrality. As a type of intensively studied materials, covalent organic frameworks (COFs) with a tunable pore structure and various functional groups are promising catalysts for CO2 RR. Herein,  COF synthesized by 2, 6‐diaminoanthraquinone and 2, 4, 6‐triformylphloroglucinol is employed to assist the synthesis of electrocatalysts from Cu single atoms (SAs) to nanoclusters by controlling the electrodeposition. A tandem catalyst for CO2 ‐to‐CH4 conversion is thus achieved by the Cu nanoclusters dispersed among the isolated Cu SAs in the COF network. It is proposed that CO2 is first reduced to CO over the atomically isolated Cu SAs, followed by diffusion onto the neighboring Cu nanoclusters for further reduction into CH4 . In addition, mechanistic analysis suggests that the coordinated K + ions on the COF network promote the activation of CO2 and the adsorption of reaction intermediates, thus realizing the suppressed hydrogen evolution reaction and selective production of CH4 . This study presents a new insight of COFs for the confined synthesis of a tunable SA to nanocluster electrocatalysts, disclosing the great potential of COFs in electrocatalysis. Abstract : Under the background of carbon neutralization, the electrochemical reduction reaction of CO2 (CO2 RR) into value‐added chemicals is a promising route to simultaneously enable a closed carbon energy cycle and curtail dependency on fossil fuels. Herein, tandem catalysis for CO2 ‐to‐CH4 conversion is realized by the Cu nanoclusters dispersed among the isolated Cu single atoms in the covalent organic framework network, paving the way for CO2 RR toward carbon neutrality.